The biodiversity of traditional leafy vegetables - Chweya, J.A.; Eyzaguirre, Pablo B.; International Plant Genetic Resources Institute (1999)
There is an undervalued reservoir of diversity of African Leafy Vegetables. These vegetables are extremely important for food security, nutrition and poverty alleviation throughout Africa. However, the reservoir is under threat because the vegetables are being displaced in many areas. There is a decline in the production, utilization and diversity of these vegetables. The decline will have a significant impact on the nutritional status of households and incomes of women farmers who are the primary producers, transformers and sellers of these plants. In response to this threat to Africa's crop genetic diversity and its food security, IPGRI convened several workshop where national plant genetic resources programmes could identify priority species and carry out actions to stem this threat. The results of those actions are contained in this book, which is the latest step forward in the commitment IPGRI has to the conservation and sustainable utilization of genetic resources in Africa. The book contains authored chapters by national scientists on the diversity and uses of leafy traditional vegetables in Botswana, Cameroon, Kenya, Senegal and Zimbabwe. The conclusions outline ways that the great potential of Africa's plant genetic resources that can be used to improve the welfare of African communities.